The effect of family relationship towards the academic achievement of secondary school students in Sebha, Libya / Zinab Abdalla Salem Lallouh - Zinab Abdalla, Salem Lallouh (2017)
This study focuses on the following questions: What is the relationship between family treatment and educational achievement? How do independent demographic variables affect family treatment? What are the general views and attitudes of the respondents about family treatment? What are the suggestions of negative family variables effect on the student’s achievement? Based on this, the study determined its aims in examining the relationship between family treatment and educational achievement, it also identified the impact of demographic independent variables in family treatment. Further, the study explored the general views and attitudes of the respondents about family treatment; it also suggested appropriate solutions for negative family variables.The nature of the study and the inclusion of theoretical and practical aspects hindered the researcher from maintaining a balance of the page numbers of chapters. The sample of study consisted of 340 students, 170 males and 170 females. The study followed analytical, descriptive approach to describe and analyze the data qualitatively and quantitatively. Some statistical tests were used like Cronbach’s alpha, frequencies, percentages, descriptive analysis of demographic data and respondents’ general views and attitudes, T-test, linear regression, factor analysis and Spearman correlation coefficient. Social survey methodology using sample was used in this study, because survey is considered to be the suitable way to collect data from the participants. The findings revealed that the effect of demographic variables on family treatment as follows size and also the monthly income of the family, father’s educational level was the third variable that affected the family treatment. The final variable was a mother’s occupation. The results of this study indicated that the relationship of students’ educational achievement with family treatment influenced by two factors (supervision, guiding and consulting)and (family relationship). Moreover, the respondents’ views about family treatmentwas that there were clear supervision and guiding from the family as the parents treated their children in good manner and their relation was good. The family treatment was equal between them and it was based on love and cooperation.The participants also acknowledged that their parents were the cause of their educational level enhancement.The study revealed some suggestions and solutions through percentages from the perspective of the study’s participants about the negative effect of family on students’ achievement. Therefore, it indicated that the parents should haveto exert more efforts in following up and guiding their children to improve their level of achievement. It also directed their children to exploit the Internet in their educational purposes. Further, the parents should manage and plan for their social visits in order to enhance their childrenachievement level.